Utilisation of media technologies for distance and lifelong education in Africa (2014)
Media technologies of television, radio, computer and internet offer flexible and formidable facilities for open distance education and lifelong education for Africa. Yet benefits of these media in attaining goals of distance and lifelong education face challenges of policy issues and organisation.